Avaliaç\~ao dos impactos regionais do Fundo Constitucional de Financiamento do Norte entre 2004 e 2010 - Guilherme Mendes Resende (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The paper aims to evaluate the economic impact of the North Constitutional Regional Fund (FNO). The study uses different spatial scales to analyse the impact of FNO on gross national product (GDP) per capita growth between 2004 and 2010. In sum, the fixed effects panel data estimations show that that FNO-sectoral impacts positively GDP per capita growth at municipal level, probably because of loans granted to rural and services sectors. The results for micro and mesorregions suggest that FNO-total and FNO-sectoral do not stimulate economic growth in more aggregated regions.
Keywords: C52; R58; 330; impact evaluation; regional development; FNO; North; Brazil